Digital Ideological Sovereignty in the Age of Platform Capitalism: A New Theoretical Approach Based on the Indonesian Case - Muhammad Falah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
This article introduces Digital Ideological Sovereignty (DIS) as a theoretical framework for understanding state power in digital spaces, emphasizing the ideological, symbolic, and relational dimensions of sovereignty. While traditional digital sovereignty focuses on infrastructure, data, and regulatory control, DIS foregrounds how states actively embed, project, and negotiate ideology in algorithmically mediated environments. To empirically ground this framework, Indonesia serves as a case study, employing a qualitative, multi-method approach including content analysis of official digital communications, platform governance documents, and social media campaigns, combined with semi-structured expert interviews with policymakers and platform managers. The study demonstrates how a Global South state leverages national ideology (Pancasila) across digital channels to maintain legitimacy, visibility, and symbolic authority. Findings reveal that ideology is performative and measurable, enacted through content framing, platform negotiation, and algorithmically optimized messaging. Importantly, DIS highlights relational sovereignty, where states do not isolate networks but strategically adapt to platform logics to amplify ideological influence. Compared to Western contexts, where digital governance often prioritizes regulation, data protection, or market competition, DIS demonstrates the centrality of ideology in sustaining legitimacy in Global South states. The framework identifies three interconnected dimensions of sovereignty material, regulatory, and ideological and operationalizes them through instruments such as official digital communications, platform compliance negotiation, and symbolic interventions. By integrating content, visibility, and symbolic authority, DIS provides a measurable and strategic approach for analyzing how states negotiate transnational platform dominance while preserving national ideological frameworks.